2001
DOI: 10.1016/s0550-3213(01)00314-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantized bulk scalar fields in the Randall–Sundrum brane model

Abstract: We examine the lowest order quantum corrections to the effective action arising from a quantized real scalar field in the Randall-Sundrum background spacetime. The leading term is the familiar vacuum, or Casimir, energy density. The next term represents an induced gravity term that can renormalize the 4-dimensional Newtonian gravitational constant. The calculations are performed for an arbitrary spacetime dimension. Two inequivalent boundary conditions, corresponding to twisted and untwisted field configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 38 publications
(43 reference statements)
1
106
1
Order By: Relevance
“…Especially the detailed studies in the Randall-Sundrum model have shown the major contribution of the Casimir effect to stabilise the radion [22,23,24,25].…”
mentioning
confidence: 99%
“…Especially the detailed studies in the Randall-Sundrum model have shown the major contribution of the Casimir effect to stabilise the radion [22,23,24,25].…”
mentioning
confidence: 99%
“…The boundary condition for the mode functions is obtained by integrating the field equation near the brane. In a way similar to that used in [19][20][21], it can be seen that for fields even under the reflection with respect to the brane (untwisted scalar field) the boundary condition is of the Robin type with…”
Section: (325)mentioning
confidence: 97%
“…In braneworld models on AdS bulk, the presence of branes gives rise to additional boundary conditions on the operator of a quantum field. These conditions depend on the specific geometry of the brane and have been discussed in [19][20][21] for models with Z 2 symmetry. Another type of boundary conditions is induced by the presence of compact spatial dimensions.…”
Section: Jhep11(2015)092mentioning
confidence: 99%
See 1 more Smart Citation
“…For the coefficients in the boundary conditions one has (see also Ref. 16 for the case c 1 = c 2 = 0)…”
Section: Quantum Effects In Higher-dimensional Cosmological Models 171mentioning
confidence: 99%